Humanizing Vilnius old town by the sump measures: when less is more - Burinskienė, Marija; Vabuolytė, Vaida; Stauskis, Gintaras (International Conference “Environmental Engineering”, 2020)
The Old Town of Vilnius City is a valuable site included in the UNESCO World Heritage List. One of the most important tasks is to protect the area from noise, pollution, and vibration caused by transport. Currently, over 30,000 vehicles cross the Old Town core daily, most of which do not have a destination in the Old Town, and drivers only use a shorter route to connect within the city. To this purpose, the Vilnius City Municipality has developed a Loop Traffic Scheme in the Old Town of Vilnius, which allows only loop traffic, i.e. for entry/exit to/from a specific restricted area. The main purpose of the article is the discussion and evaluation of measures how the Old Town area can be returned to the people (i.e., pedestrians, cyclists, public transport) to minimize traffic flows and eliminate transit traffic. To achieve smart solutions and to open public spaces for Old Town residents and visitors, we compare different traffic organization and parking measures, analyse their efficiency. We propose integrating innovative technological solutions and smart tools (parking, ridesharing system, integrated pedestrian and bicycle routes, smart traffic control, etc.) by using the best practices of other cities. As a result, we propose the methodology for humanizing open spaces in the Old Town area and beyond.